1998
DOI: 10.1580/1080-6032(1998)009[0198:nisita]2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy in the assessment of cerebral oxygenation at high altitude

Abstract: Hypoxia plays a key role in the pathogenesis of acute mountain sickness (AMS), but individual susceptibility is variable and cerebral symptoms do not always correlate with PaO2 measurements. Cerebral hypoxia may be more relevant than PaO2. We studied trends in cerebral regional oxygen saturation by the technique of near-infrared spectroscopy in 20 subjects ascending rapidly to 4680 m. Subjects were enrolled in a placebo-controlled, double-blind trial of medroxyprogesterone for the prevention of AMS. The fall i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
1
21
1
Order By: Relevance
“…The NIRS method is particularly suitable for multiple measurements of trends rather than single absolute measurements of cerebral oxygenation. We have reported the changes observed on ascent to high altitude and found that the equipment was robust and suitably sensitive for use in the field [15]. In the present study the acute effects of CO # -enriched air on peripheral and cerebral regional oxygenation at high altitude are reported, and the results obtained with CO # are compared with the effects of hyperventilation and administration of oxygen.…”
Section: Introductionmentioning
confidence: 91%
“…The NIRS method is particularly suitable for multiple measurements of trends rather than single absolute measurements of cerebral oxygenation. We have reported the changes observed on ascent to high altitude and found that the equipment was robust and suitably sensitive for use in the field [15]. In the present study the acute effects of CO # -enriched air on peripheral and cerebral regional oxygenation at high altitude are reported, and the results obtained with CO # are compared with the effects of hyperventilation and administration of oxygen.…”
Section: Introductionmentioning
confidence: 91%
“…Impairment in control of cerebral perfusion can cause cerebral ischaemia, with potentially grave consequences (Roach & Hackett, 2001). In healthy lowlanders ascending rapidly to high altitude, non-invasive near-infrared spectroscopy (NIRS) studies using sensors placed on the scalp revealed a considerable reduction in cerebral tissue oxygenation (CTO; Imray et al 1998;Wilson et al 2011;Rupp et al 2014). Whether CTO is also reduced in lifelong residents at high altitude has not been studied, although this might elucidate mechanisms of chronic altitude adaptation and it may guide future research to identify targets for prevention and treatment of altitude-related illness associated with cerebral dysfunction (León-Velarde et al 2005;Wilson et al 2009;Vermeij et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral spectroscopy has been shown to track changes in jugular venous bulb saturations in healthy volunteers under conditions of isocapnic hypoxia (12) and has also been validated by comparison with PET scanning, with 133 Xe washout methods and with internal carotid artery stump pressures (54). We have used this technique during dynamic studies of cerebral oxygenation at altitude and assessed the effects of hyperventilation, oxygen therapy, and CO 2 supplementation (19,20) and during assessment of the effects of pressurization in a portable hyperbaric chamber (21). Assessments of cerebral blood flow and cerebral oxygenation during exercise and under field conditions have proven challenging.…”
mentioning
confidence: 99%